2012
DOI: 10.1007/s13311-011-0087-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Treatment Targets for Cerebral Edema

Abstract: Cerebral edema is a common finding in a variety of neurological conditions, including ischemic stroke, traumatic brain injury, ruptured cerebral aneurysm, and neoplasia. With the possible exception of neoplasia, most pathological processes leading to edema seem to share similar molecular mechanisms of edema formation. Challenges to brain-cell volume homeostasis can have dramatic consequences, given the fixed volume of the rigid skull and the effect of swelling on secondary neuronal injury. With even small chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 97 publications
(94 reference statements)
1
83
0
Order By: Relevance
“…Accordingly, expression of SUR1 is up-regulated in reactive astrocytes, neurons, and capillaries of rodent models for ischemia, traumatic brain injury, and spinal cord injury (11,12,(43)(44)(45). The effects of trauma appear to be reduced by administration of glibenclamide (46,47); clinical trials to test the potential of this antidiabetic drug as a treatment for brain edema are under way (48), but the subject remains controversial (49,50). On the other hand, fragmentation and hemorrhaging in capillaries correlate with an increase in TRPM4 expression in rats after spinal cord injury and are significantly mitigated in TRPM4-null mice (17).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, expression of SUR1 is up-regulated in reactive astrocytes, neurons, and capillaries of rodent models for ischemia, traumatic brain injury, and spinal cord injury (11,12,(43)(44)(45). The effects of trauma appear to be reduced by administration of glibenclamide (46,47); clinical trials to test the potential of this antidiabetic drug as a treatment for brain edema are under way (48), but the subject remains controversial (49,50). On the other hand, fragmentation and hemorrhaging in capillaries correlate with an increase in TRPM4 expression in rats after spinal cord injury and are significantly mitigated in TRPM4-null mice (17).…”
Section: Discussionmentioning
confidence: 99%
“…In the 2012 pediatric TBI guidelines, there was greater evidence of effect for HTS than for mannitol [15]. Several studies have shown equipoise in the efficacy of mannitol in reducing mortality in head injury [16] and others found HTS was superior [17].…”
Section: Discussionmentioning
confidence: 99%
“…93 However, none of these treatment strategies have been widely translated to human patients. 32 Species-specific differences in brain structure and function, lack of sex heterogeneity, and a shortage of trials in the setting of relevant comorbidities are potential reasons for translational failures.…”
Section: Barriers To Implementation Of Neuroprotective Strategiesmentioning
confidence: 99%